(untitled) - Ho, Thi Van (Can Tho, 2014)
The study is carried out to investigate curren pre-speaking activities of grade 10 English classes at Thot Not high school
Keywords: Ngôn ngữ Anh,English language; Dạy và học,Study and teaching